Smart Garbage Bin - J, Deepika K; S, Lakshmi V; R, Pooja; S, Rakshitha B; M, Amala (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2017)
The absence of efficient waste management as caused serious environmental problems and cost issues. We here propose a probable solution to this problem, an automatic garbage level detecting system informing the concerned authorities timely and also the periodic data for a month of each bin is stored in a micro SD card which can be used for analysis of garbage management more efficiently and effectively. Here we are going to place ultrasonic distance measurement sensor in the dustbin which measures the amount of garbage collected and sense continuous information to the centralized control system situated in the municipal office and a capacitive sensor to segregate wet and dry waste. This model consists of an Arduino controller, a garbage bin loaded with sensors and they are monitored continuously through a web. This system also has a scope for citizen participation, wherein any grievances from citizens related to waste management is heard.